Effects of Genotype and Housing System on the Laying Performance of Chickens in Different Seasons in the Semi-Humid Tropics - Yakubu, A.; Salako, A.E.; Ige, A.O. (International Journal of Poultry Science, 2007)
An experiment was designed to study the effects of genotype and housing system on the performance of two commercial layers, Bovans Brown and Lohmann Brown in the hot-dry and wet seasons in Lafia, Nasarawa State, Nigeria. Six hundred, 27 week-old layers were used. One hundred and fifty birds of each strain were randomly assigned to the battery cage system, while another one hundred and fifty birds of each strain were managed on deep litter. The observation for the hot-dry and wet seasons lasted 2 months each respectively in the year 2004. Body weight, hen-housed egg production, egg weight and mortality rate were significantly better in Lohmann Brown than Bovans Brown (1.75±0.01kg vs. 1.69±0.01kg, 74.50±0.84% vs. 68.72±0.86%, 53.70±0.24g vs. 52.43±0.26g, 0.58±0.09% vs. 1.20±0.15%; p<0.05). Birds in cages were superior to those on deep litter in terms of hen-housed egg production, egg weight and mortality (74.06±0.75% vs. 69.16±1.02%, 53.40±0.24g vs. 52.73±0.29g, 0.68±0.10% vs. 1.10±0.15%; p<0.05). Generally, birds performed better in the wet than hot-dry season in body weight, hen-housed egg production, feed intake, egg weight, egg cracks and mortality (1.76±0.01kg vs. 1.68±0.01kg, 74.92±0.74% vs. 68.30±0.86%, 98.51±0.50g vs. 90.90±0.23g, 53.92±0.18g vs. 52.22±0.27g, 1.99±0.23% vs.5.12±0.39%, 0.55±0.08% vs. 1.22±0.15%; p<0.05). The interactions between genotype×housing system, genotype×season and housing system×season produced significant results. Proper housing design, provision of quality and adequate feeds and proper timing of the laying period were recommended.